Education, technology and creative industry: a case study of Wattpad - Coelho, Patrícia Margarida Farias (2021)
This article investigates the use of Wattpad application, launched in 2006, in upper secondary Portuguese language classes as an educational tool for reading and writing texts. This study has two objectives: (i) to present the main usability characteristics of Wattpad and (ii) to propose possible implementation actions of the application as a didactic-pedagogical tool in upper secondary education. To this end, we present a case study in which we assessed the first and the latest written productions on Wattpad platform of 22 sutdents aged 15 to 17 years, attending the 1st year of upper secondary education in the same classroom of São Paulo state education system.